2021
DOI: 10.1016/j.stemcr.2021.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Flux Experiments for Quantitative Modeling of Normal and Malignant Hematopoietic Stem/Progenitor Dynamics

Abstract: Summary Hematopoiesis serves as a paradigm for how homeostasis is maintained within hierarchically organized cell populations. However, important questions remain as to the contribution of hematopoietic stem cells (HSCs) toward maintaining steady state hematopoiesis. A number of in vivo lineage labeling and propagation studies have given rise to contradictory interpretations, leaving key properties of stem cell function unresolved. Using processed flow cytometry data coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Self-renewal and differentiation capacities are particularly relevant to leukemia research, which, in most cases, struggles with identifying cell types of cancer origin. As we show here and supported by previous studies (Busch et al, 2015; Takahashi et al, 2021), progenitors can also operate close to self- renewal and a small proliferative advantage may be sufficient to immortalize them. Finally, population dynamic models are universally applicable across biological fields, as adult tissues are commonly replenished from their own stem cell pools (Goodell et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Self-renewal and differentiation capacities are particularly relevant to leukemia research, which, in most cases, struggles with identifying cell types of cancer origin. As we show here and supported by previous studies (Busch et al, 2015; Takahashi et al, 2021), progenitors can also operate close to self- renewal and a small proliferative advantage may be sufficient to immortalize them. Finally, population dynamic models are universally applicable across biological fields, as adult tissues are commonly replenished from their own stem cell pools (Goodell et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The reason for this choice lays in 2 observed characteristics in the data: cluster 0 ratio of labelled to unlabeled cells (labelling frequency) grows over time, and some downstream clusters’ labelling frequency overshoots the one in cluster 0. Based on (Barile et al, 2020) and (Takahashi et al, 2021), this implies that the progenitor cluster must be heterogeneous. Indeed, the most immature HSCs occupy only the tip of cluster 0 (Figure 2C).…”
Section: Methodsmentioning
confidence: 99%
“…However, finding a specific marking of HSC is also challenging. Currently, the iFgd5 is thought to be the best model regarding specificity and recombination efficiency compared to Tie2, Pdzk1ip1, or KRT18 (19,27,(40)(41)(42). Additionally, intrauterine labeling is less efficient than postnatal p2 marking as Figure S3D.…”
Section: Discussionmentioning
confidence: 99%
“…Both a study of somatic mutations in a 115-yr-old woman and a recent longitudinal study following the evolution of clones in an individual from age 103 to 110 (3 time points) found that likely benign clones achieved VAFs of up to 0.3 (van den Akker et al, 2020; Holstege et al, 2014)-suggesting a very small pool of stem cells. Another possible explanation is that the observed variants arose in cells with faster rates of self-renewing symmetric divisions λ , either due to natural selection of faster dividing HSPCs or because the observed variants in the LBC arose in different HSPC compartments, such as multipotent progenitor cells (Barile et al, 2020; Morcos et al, 2020; Takahashi et al, 2021). Since we can only directly measure θ , it is possible that both a depletion of the pool of HSPCs at old age and heterogeneity in the self-renewal rate λ have enabled neutral events to reach high VAFs.…”
Section: Discussionmentioning
confidence: 99%